2015
DOI: 10.6002/ect.tdtd2015.p66
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Kazakhstan is experiencing a high demand for liver transplants. More than 1000 patients have end-stage liver disease in the country, and liver transplant is the only viable option for their treatment. Conclusions: Our experience was insufficient to adequately assess morbidity and survival rates in patients for whom the longest follow-up was 25 months. However, no episodes of rejection were observed. Survival rates between living and deceased donor recipients were equivalent, although cadaveric-dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…18 Another study from the National Oncology Center in Nur-Sultan reported 30 patients with liver cirrhosis due to HBV and HBV+HDV infections, and four cases of HCV infection among 64 transplantations carried out at the center. 19,20 These reports with high rates of viral hepatitis among transplant referrals indicate the need to identify the true prevalence of viral hepatitis to implement policies for reducing the burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another study from the National Oncology Center in Nur-Sultan reported 30 patients with liver cirrhosis due to HBV and HBV+HDV infections, and four cases of HCV infection among 64 transplantations carried out at the center. 19,20 These reports with high rates of viral hepatitis among transplant referrals indicate the need to identify the true prevalence of viral hepatitis to implement policies for reducing the burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Living donation is the most attractive option in solving the organ shortage problem [ 7 ]. In Kazakhstan, the first successful liver transplantation from a living donor was performed in 2011 in collaboration with a transplant team from Belarus [ 8 ]. Since 2013, liver transplantation numbers have been steadily increasing in transplant centers of Kazakhstan ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%